Institutional Synergy Model in Development Tourism Village in East Lombok Regency - Wahyunadi Wahyunadi; Mansur Afifi; M.Firmansyah M.Firmansyah (UIN Sunan Gunung Djati, 2021)
The objectives to be achieved in this research were to describe the pattern of institutional synergy and the factors that determine the synergy between institutions/stakeholders in developing Tourism Villages in East Lombok Regency. This research was qualitative-quantitative prospective research in which the perception of stakeholders/institutions towards synergiesâ€”data analysis using the Qualitative Comparative Analysis (QCA) method assisted by Tosmana version 1.54 software. QCA is a new way to research social phenomena that combines the power of quantitative and qualitative methods. In this study, the QCA method was used to find a model (pattern) and causality structure between the level of synergy between institutions (stakeholders) in the East Lombok Regency. Data processing using QCA software obtained results in the form of a QCA Output Truth Table showing the contribution of each stakeholder actor in supporting the realization of institutional synergy in the development of tourist villages. The level of contribution was measured through 4Â (four) parameters. Based on the analysis of the QCA Truth Table results, the factors that form institutional synergy can be seen. These factors were based on factors that get strong support from stakeholders. The factors that received strong support from stakeholder actors were: responsibility (v4), strategic vision (v1), capacity (v2) and mindset (v3 ). The responsibility factor (v4) received a strong contribution from 7 stakeholders, the strategic vision factor (v1)Â received strong support from 6 stakeholders, the capacity factor (v2) received a strong contribution from 5 stakeholders, and the mindset factor (v3) received moderate support from 3 stakeholders.